2015
DOI: 10.1111/cga.12107
|View full text |Cite
|
Sign up to set email alerts
|

Causes of the failure and the revision methods for congenital scoliosis due to hemivertebra

Abstract: The purpose of this study was to retrospectively investigate the causes of failure in the first operation and the revision procedure for patients with congenital scoliosis due to hemivertebra. Nineteen patients who underwent the revision operations because of failure in the first operation were included in this study. All the malformations were identified as fully segmented hemivertebra, including 16 cases in thoracolumbar vertebra (T10: three patients; T12: seven patients; L1: six patients), and three cases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Although the type and cause of deformity are various, these progressive deformities reported in previous literature have a common ground, that the postoperative deformity develops on the hemivertebra resection level or surgical fusion area [8,12,14,16]. In contrast, the progressive curve developing in present congenital patients actually have little correlation with the initial surgical segment.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Although the type and cause of deformity are various, these progressive deformities reported in previous literature have a common ground, that the postoperative deformity develops on the hemivertebra resection level or surgical fusion area [8,12,14,16]. In contrast, the progressive curve developing in present congenital patients actually have little correlation with the initial surgical segment.…”
Section: Discussionmentioning
confidence: 92%
“…With the wide application of posterior hemivertebra resection and short fusion, the number of these cases has steadily increased, and the surgical complications have gradually become another prominent problem besides deformity correction by surgery itself [8,12,[14][15][16]. The postoperative new deformity is one of the most common complications in this surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shi Z et al investigate the causes of failure in the rst operation and the revision procedure for patients with congenital scoliosis due to HV [19]. They suggested that limitations of the primary surgery, no or incomplete resection of HV, improper operation during surgery, improper internal xation material and xation scope were main cause of revision surgery.…”
Section: Discussionmentioning
confidence: 99%